(untitled) (Palíndromo, 2025)
I’ve been thinking a lot about tearing and sprouting from a place of lack. What I present here is an essay composed of scavenged photographs that, once torn, generate mountain-like movements from which organic vitality emerges. Is it drawing? Painting? Collage? It’s a blend of memory and Latin American magical realism. It is a living reforestation, where anonymous people are transformed, hybridized, and reconnected with the nature of existing — and re-existing — on this planet. As a transvestigender artist, I inhabit a hybrid existence, and my research is deeply rooted in hybridity. As a nearsighted artist, I see things blurred and blended. My way of seeing and being gives rise to these disobedient figures, which reject fixed forms and categories, and germinate new possibilities of being — part plant, part human, part dream.